Neuronal Calcium Signaling in Metabolic Regulation and Adaptation to Nutrient Stress - Jayakumar, Siddharth; Hasan, Gaiti (Frontiers in Neural Circuits, 2018)
All organisms can respond physiologically and behaviourally to environmental fluxes in nutrient levels. Different nutrient sensing pathways exist for specific metabolites, and their inputs ultimately define appropriate nutrient uptake and metabolic homeostasis. Nutrient sensing mechanisms at the cellular level require pathways such as insulin and TOR signalling that integrates information from different organ systems like the fat body and the gut. Such integration is essential for coordinating growth with development. Here we review the role of a newly identified set of integrative interneurons and the role of intracellular calcium signalling within these neurons, in regulating nutrient sensing under conditions of nutrient stress. A comparison of the identified Drosophila circuit and cellular mechanisms employed in this circuit, with vertebrate systems, suggests that the identified cell signalling mechanisms may be conserved for neural circuit function related to nutrient sensing by central neurons. The ideas proposed are potentially relevant for understanding the molecular basis of metabolic disorders, because these are frequently linked to nutritional stress.